Bioassay-guided isolation and antiproliferative efficacy of extract loaded in chitosan nanoparticles and LC-QTOF-MS/MS analysis of Achillea magnifica - TAŞKIN, TURGUT (ELSEVIER, 2020)
This study investigated the antioxidant, anti-urease, anticholinesterase, and antiproliferative activities of different extracts of A. magnifica. The active compounds were isolated from chloroform extract, which has the strongest antiproliferative and antioxidant activities. The structures of the isolated compounds (elenolic acid, luteolin, eupatilin) were examined using spectroscopic techniques (NMR, UV, HR-MS). The antioxidant and antiproliferative effects of isolated compounds showed lower biological activity than those of the chloroform extract. Therefore, chitosan nanoparticles were prepared with this extract and characterized. The cytotoxic activities of the chitosan nanoparticles were examined, and they were found to have a strong antiproliferative activity similar to that of the chloroform extract. The ethanol extract had strong anti-urease and anticholinesterase activity compared with other extracts. Therefore, phenolic compounds that might be responsible for the biological activity were analysed by LC-QTOF-MS/MS. The ferulic acid derivative, apigenin 6 C pentoside 8 C hexoside, apigenin 6,8-di C-hexoside, vitexin, and diosmetin 8-C-glucoside (orientin 4'-methyl ether) compounds from this plant were analysed for the first time. The results showed that the chloroform-loaded chitosan nanoparticles had a strong antiproliferative activity in breast cancer cell lines (MCF-7, MDA-MB-231) and no toxic effect on normal cell lines (L-929), which suggested that this extract might be a potential candidate as a herbal medicine that can be investigated and evaluated in future cancer studies. Additionally, the potential use of ethanol extract as an anti-urease and anticholinesterase agent was revealed. (C) 2020 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: A. magnifica; Chitosan nanoparticles; Biological activity; LC-QTOF-MS/MS; ANTIOXIDANT ACTIVITY; ESSENTIAL OILS; FLAVONOIDS; SYSTEM